METHOD OF PRODUCING DISPERSION LIQUID OF GELATINOUS ELECTROLYTE - ENDO YOSHITO (2016)
The present invention relates to a method for producing a gel-phase electrolyte dispersion. The method for producing the gel-phase electrolyte dispersion includes a moisture content reduction process and an alcohol addition process. In the moisture content reduction process, a water-based dispersion of an electrolyte is concentrated at a temperature below 50 °C, and the content of moisture in the electrolyte concentrate is reduced to less than or equal to 5 wt%, with respect to the total mass of the electrolyte concentrate. In the alcohol addition process, the gel-phase electrolyte dispersion is formed by addition of alcohol into the electrolyte concentrate obtained form the moisture content reduction process. 본 발명의 겔상 전해질 분산액의 제조 방법은, 전해질의 수성 분산액을 50℃ 이하의 온도에서 농축하고, 상기 전해질 농축물 중의 수분 함량을, 상기 전해질 농축물의 총 질량에 대하여 5질량％ 이하가 될 때까지 저하시키는, 수분 함량 저하 공정과, 이 수분 함량 저하 공정에서 얻어진 전해질 농축물에 알코올을 첨가하여, 겔상 전해질 분산액을 형성시키는, 알코올 첨가 공정을 포함한다.